(untitled) (Texas Journal of Philology, Culture and History, 2026)
The article is devoted to the study of the concept of time in Russian and Uzbek linguocultures from the perspectives of cognitive linguistics and linguoculturology. The theoretical foundations of concept modeling, its axiological function, and methods of its indirect measurement through linguistic representations are examined. The empirical basis of the study is constituted by data obtained from an associative survey of native speakers. The comparative analysis demonstrates the combination of the universality of the temporal category with the national specificity of its interpretation